A Semiotic Analysis in Who Killed Sara Film (2021) - Dipratama, Garda Muhammad Fadhillah; Saefudin, Saefudin (English Department, Faculty of Humanities, Andalas University, 2023)
This article aims to (1) to find out the connotative and denotative of meaning in the film Who Killed Sara (2) to determine the forms of gender discrimination which appear in Who Killed Sara. Researcher uses Roland Barthes’s Semiotics theory to identify the Gender discrimination form that appear through the film Who Killed Sara. After the deep research, the researcher founds that (1) the meaning of gender discrimination is highlighted by the discriminatory treatment of women in public life. When a group of people imposes restrictions on the social life of a woman, their view of the weakness and low status of women also leads women to experience discrimination (2) the form of discrimination that appear through the film has many varieties, such as; violence (verbal and non-verbal), stereotype, subordination, and workload. From this film, it can be seen that acts of discrimination are heinous acts and have a bad impact on a person. So this film provides a moral message for us viewers to create gender equality in social life.